2006
DOI: 10.4081/ijas.2006.393
|View full text |Cite
|
Sign up to set email alerts
|

Cultural energy analysis on broilers reared in different capacity poultry houses

Abstract: Data obtained from 4 different capacity houses were evaluated to analyse the cultural energy and perfor- mance of broilers. Capacities of housings were 20,000, 25,000, 30,000 and 60,000 birds per production peri- od and they were assigned as HI, HII, HIII and HIV, respectively. The study was conducted in 2005 in which there were 6 production periods of 45 days. Data collected for each period were: date of starting and finish- ing; number of chicks entered and broilers sold; live weight at slaughter; carcass we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 8 publications
3
12
0
Order By: Relevance
“…This reduction in feed consumption as in poultry house size increased may relate on high conversion efficiency. These results are in agreement with Atilgan and Hayati (2006), who showed that housing capacity increases CE expended per kg of weight gain, and per Mcal of protein energy output decreases in 30,000 birds but increased in 60,000 birds. CE expended on electricity increased as housing capacity increased.…”
Section: Results and Disscusionsupporting
confidence: 93%
“…This reduction in feed consumption as in poultry house size increased may relate on high conversion efficiency. These results are in agreement with Atilgan and Hayati (2006), who showed that housing capacity increases CE expended per kg of weight gain, and per Mcal of protein energy output decreases in 30,000 birds but increased in 60,000 birds. CE expended on electricity increased as housing capacity increased.…”
Section: Results and Disscusionsupporting
confidence: 93%
“…Moreover, many researchers worldwide have studied EUE in the poultry production sector, including broiler (Sibbald 1982;Andrews & Zimmermann 1990;Grobas et al 1999;Atilgan & Koknaroglu 2006;Jekayinfa 2007;Heidari et al 2011a) and laying hens (Ojo 2003;Yusuf & Malomo 2007;Ashagidigbi et al 2011, Sefeedpari et al 2012. However, there have been no studies related to the EUE of egg production and comparison of energy uses in laying hens and broiler production farms in Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…These factors have encouraged an increase in energy inputs to maximize growth, feed efficiency and profitability, to minimize labour-intensive practices, or both (Atilgan & Koknaroglu 2006;Esengun et al 2007). Efficient energy use in the poultry production is as significant as in agricultural production due to its potential to provide financial savings, preserve fossil fuel resources and reduce air pollution (Uzal 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Feeding accounts about 70% of the cost of production, which can sometimes rise up to 80% [3] [4] and this high cost created the need to improve the efficiency of feed utilization. This experiment was designed to implement feed restriction programs in order to control the increase of carcass weight to be within the preferable market weight (1100 -1200 g/bird) and to determine the economic impact of these programs.…”
Section: Introductionmentioning
confidence: 99%